An Analysis of Educational Quality Management Strategies for Improving School Accreditation at SMK Negeri 1 Penukal Utara - Ramdhani, Iqbal; Sabila, Ade Sintia Arsy; Imani, Naila Putri; Marlina, Leny; Febriyanti, Febriyanti (The Future of Education Journal, 2025)
This study aims to analyze the educational quality management strategies implemented at SMK Negeri 1 Penukal Utara in an effort to improve the school’s accreditation status. The research adopts a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation. The primary informants included the principal, vice principals, teachers, and the accreditation team. The findings reveal that the school implements quality management strategies through work program planning based on self-evaluation, enhancement of teacher competencies, utilization of information technology, and involvement of stakeholders in the quality improvement process. Key supporting factors in implementing these strategies include the commitment of school leadership, resource availability, and synergy among school members. Challenges encountered include budget limitations and resistance to change. The study concludes that consistently and collaboratively applied quality management strategies can significantly contribute to improving school accreditation.